PENGARUH ZAKAT, INFLASI DAN PERKEMBANGAN USAHA MIKRO KECIL MENENGAH TERHADAP PERTUMBUHAN EKONOMI TAHUN 2011-2018 (STUDI KASUS DI INDONESIA) - Musalim Ridlo; Dwi Setyani (Universitas Teuku Umar, 2020)
This research aims to analyze the influence of zakat, inflation and the development of micro small and medium enterprises (UMKM) to economic growth in the Indonesia period 2011-2018. This research uses quantitative approach methods. This research is a secondary study of data time series that was subsequently analyzed using the EVIEWS 09 application. The data used ate quarterly data on zakat, inflation and the development of micro small and medium enterprises and gross domestic product (PDB) period 2011-2018. The results of this research show that zakat has a positive and insignificant effect, Inflation has negative and insignificant, and the development of micro small and medium enterprises (UMKM) has a positive and insignificant effect to economic growth in Indonesia. Simultaneously zakat, development of micro (UMKM) has a significant and insignificant to economic growth.Keywords: Zakat, Inflation, the development of UMKM, Economic Growth